Interatrial pressure gradients during simulated obstructive sleep apnea: A catheter‐based study. Issue 7 (11th March 2014) - Konecny, Tomas; Khanna, Amber D.; Novak, Jan; Jama, Abdi A.; Zawadowski, George M.; Orban, Marek; Pressman, Gregg; Bukartyk, Jan; Kara, Tomas; Cetta, Frank; Borlaug, Barry A.; Somers, Virend K.; et al.
<x xml:space="preserve">Abstract</x> Objectives We set to measure the interatrial pressure gradient during simulated obstructive sleep apnea (OSA). Background OSA occurs when a sleeping patient attempts to inhale against an obstructed airway. How this event affects the interatrial pressure gradient has not been defined. We hypothesized that simulated OSA in a conscious subject (Mueller maneuver [MM], inspiration against obstruction) would promote increased right‐to‐left pressure gradient, and then the substrate for right‐to‐left atrial shunting. Methods Selected patients underwent simultaneous measurement of airway and atrial pressures (both left and right atrium [LA, RA]) using high‐fidelity micromanometry at rest, during MM, and during VM, during right heart catheterization. Results Ten patients (age 55 ± 11 years, two women) were successfully studied. During the onset of MM, RA pressure transiently but consistently exceeded LA pressure in response to the steep decline in intrathoracic pressure (maximum RA‐LA pressure gradient increased from 0.1 ± 1.4 mm Hg at baseline to 7.0 ± 4.3 mm Hg during MM, P < 0.001). The maximum right‐to‐left atrial pressure gradient during Mueller maneuver was higher than that achieved during the Valsalva maneuver release (P < 0.007). Conclusions The onset of MM increased right‐to‐left pressure gradient across the atrial septum, likely as a result of greater blood return to the RA from extrathoracic veins. The RA‐LA pressure gradient achieved during MM was greater than that observed during VM. These findings delineate the hemodynamic substrate for right to left shunting during OSA. © 2014 Wiley Periodicals, Inc.